2014
DOI: 10.1007/s00415-014-7545-y
|View full text |Cite
|
Sign up to set email alerts
|

Frontostriatal dysexecutive syndrome: a core cognitive feature of myotonic dystrophy type 2

Abstract: The aim of this study was to assess cognitive status in a large group of patients with myotonic dystrophy type 2 (DM2) compared to type 1 (DM1) subjects matched for gender and age, using a comprehensive battery of neuropsychological tests. Thirty-four genetically confirmed adult DM2 patients were recruited and matched for gender and age with 34 adult-onset DM1 subjects. All patients underwent detailed classic pen and pencil neuropsychological investigation and also computerized automated battery-CANTAB. More t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 36 publications
2
24
1
Order By: Relevance
“…In a study where DM2 patients has been compared to age-matched DM1 patients, a specific type of “avoidant” personality and a significant impairment in frontal lobe function (especially limited ability to perform executive functions) have been observed in both groups of patients although these abnormalities were milder in DM2 patients [26]. Similar observations have been reported in a more recent study performed in a larger cohort of DM2 patients who showed significant dysexecutive syndrome and certain impairment of episodic verbal memory that are reflective of frontal (especially frontostriatal) and temporal lobe dysfunction [27]. At histopathological level, the analysis of post mortem DM2 brain samples showed the occurrence of a tau pathology similar to that observed in DM1 patients characterized by the presence of neurofibrillary tangles and Marinesco bodies in brain tissue [28, 29].…”
Section: Myotonic Dystrophy Typesupporting
confidence: 66%
“…In a study where DM2 patients has been compared to age-matched DM1 patients, a specific type of “avoidant” personality and a significant impairment in frontal lobe function (especially limited ability to perform executive functions) have been observed in both groups of patients although these abnormalities were milder in DM2 patients [26]. Similar observations have been reported in a more recent study performed in a larger cohort of DM2 patients who showed significant dysexecutive syndrome and certain impairment of episodic verbal memory that are reflective of frontal (especially frontostriatal) and temporal lobe dysfunction [27]. At histopathological level, the analysis of post mortem DM2 brain samples showed the occurrence of a tau pathology similar to that observed in DM1 patients characterized by the presence of neurofibrillary tangles and Marinesco bodies in brain tissue [28, 29].…”
Section: Myotonic Dystrophy Typesupporting
confidence: 66%
“…To the best of our knowledge, this is the first longitudinal study that compares DM1 and control subjects in neuropsychological terms. Although it was not the main aim of the present study to analyse the cognitive profile of DM1, a transversal comparison of both groups confirmed that the cognitive profile of our sample is in line with the pattern of dysexecutive and visuoconstructive deficits described previously in DM1, suggesting the involvement of fronto‐parietal areas (Peric et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Mild cognitive impairment or dementia due to Alzheimer's disease (AD) can present with a clinically apparent FLS [26][27][28] . Also, dementia with Lewy bodies, progressive supranuclear palsy, corticobasal degeneration, Parkinson's disease, vascular dementia and myotonic dystrophy type 2 can all result in similar symptoms [29][30][31][32][33][34][35] . Apathy, in particular, is frequently apparent in vascular dementia and Parkinson's disease [29,36] .…”
Section: Differential Diagnosismentioning
confidence: 99%